Occurrence of intestinal parasites among the teachers, students and staffs of Dhaka University - Khanum, Hamida; Rahman, Farzana; Zaman, Rimi Farhana (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present study was conducted to find out the incidence of the intestinal parasites and their prevalence among the teachers, students and staffs of University of Dhaka, Bangladesh. The study revealed that the prevalence of intestinal protozoa and helminth parasites are common among the outdoor patients of University of Dhaka. A total of 350 stool samples was examined in the Pathology department of Medical Center of University of Dhaka from June 2009 to May 2010, four species of intestinal parasites were identified of which two species were protozoa (Entamoeba histolytica and Giardia intestinalis) and two species were nematodes (Ascaris lumbricoides and Trichuris trichiura). The overall prevalence of infestation was 23.14% where Entamoeba histolytica, Giardia intestinalis, Ascaris lumbricoides and Trichuris trichiura were found as 4.86%, 3.71%, 11.14% and 3.43% respectively. Highest prevalence was recorded in Ascaris lumbricoides (11.14%) and the seasonal pattern showed that highest (30%) prevalence occurred in rainy season and lowest (17.19%) in winter season. The prevalence of intestinal parasites was higher in female (30.56%) than in male (22.29%). DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17863 J. Asiat. Soc. Bangladesh, Sci. 39(2): 239-246, December 2013